Comparison of Chemical and Enzymatic Interesterification of Tea Seed Oil for the Production of Cocoa Butter Replacer - Zarringhalami, Soheila; Ali Sahari, Mohammad; Barzegar, Mohsen; Hamidi-Esfehani, Zohre (Current Nutrition & Food Science, 2012)
Cocoa butter replacer (CBR) was produced by the chemical and enzymatic interesterification of the hydrogenated and solid fraction of tea seed oil, at weight percent ratios of 20:80, 25:75 and 30:70. At the ratio of 30:70 (hydrogenated tea seed oil: solid fraction) in both the methods of interesterification, the major fatty acids were palmitic, stearic and oleic acids (17.58, 16.89 and 44.63 %; 17.58, 16.89 and 44.56 %, respectively). Also in this ratio the melting points (m.p.) of samples produced by two methods were 30.03 ºC and 32.23 ºC, respectively. As a comparison, the ratio of 30:70 showed proximate resemblance to those of cocoa butter (25.76, 34.88 and 33.68 %; 31.43 ºC, respectively) than other ratios. The triacylglycerol species (TAGS) play a key role in producing sharp melting point of cocoa butter (one of the most important quality factors in chocolate). As results showed, the enzymatic interesterification produces the sample with the TAGS closer to those of cocoa butter (PLP, OOO, PLS, POP, SOO, POS, SOS). Therefore, it is a suitable method compared with the randomized chemical interesterification.
Keywords: fats